La enseñanza de la sexualidad infantil de los padres de familia y su influencia en el desarrollo de la personalidad de los niños y niñas de 5 a 6 años de edad en la unidad educativa “San Francisco de Asís” de la ciudad de Loja periodo 2014 - Ludeña Ojeda, Ximena Isabel (2015)
The following thesis makes review a: LA teaching LA sexuality child of LOS parents of family and his influence in the development of the personality of LOS children and girls 5 to 6 years of age in the educational unit "SAN FRANCISCO DE ASSISI" of the city of LOJA period 2014;infantile sexuality education is extremely important in the life of the infant already ranging from toddlers to learn about the subject of an involuntary and unconscious way, my sexuality goes conforming according to how I perceive my parents and what they feel themselves allowing them to form along with their everyday experiences, their own personality. The methods used for the preparation of the present research work were: science, deductive, inductive, statistical method and the descriptive. The data allowed us to carry out the discussion and comparison of the objectives and the possible alternatives of solution to the problem posed, were obtained through the application of a pedagogical survey to parents in order to obtain information about child sexuality, as also a test of apperception child cat - which allowed me to learn about the development of the personality of childrenthe total sample consisted of 31 parents and 31 children 5 to 6 years of age. After the corresponding to the data analysis, it is concluded that the teaching of infantile sexuality if it has an impact on the development of the personality of children, since the parents talk to them about the issue and are aware of how should take care of your body go at the same time building an identity own and healthy sexuality allowing them a good development of his personality.